p66Shc gene expression in peripheral blood mononuclear cells and progression of diabetic complications - Fadini, Gian Paolo (Cardiovasc Diabetol, 2018)
BACKGROUND: The risk of diabetic complications is modified by genetic and epigenetic factors. p66Shc drives the hyperglycaemic cell damage and its deletion prevents experimental diabetic complications. We herein tested whether p66Shc expression in peripheral blood mononuclear cells (PBMCs) predicts adverse outcomes in people with diabetes. METHODS: In a cohort of 100 patients with diabetes (16 type 1 and 84 type 2), we quantified baseline p66Shc expression in PBMCs by quantitative PCR. Patients were extensively characterized for demographics, anthropometrics, biochemical data, prevalence of complications, and medications. With a pseudo-prospective design, we retrieved cardiovascular death, major adverse cardiovascular events (MACE), and new occurrence of micro- or macroangiopathy during follow-up. RESULTS: At baseline, patients were on average 60 year old, with 10-year diabetes duration, and overall poor glycaemic control (HbA1c 7.8%). Patients with high versus low p66Shc expression (based on median value) had very similar baseline characteristics. Average p66Shc expression did not differ by presence/absence of complications. During a median 5.6-year follow-up, the primary endpoint of cardiovascular death or MACE occurred in 22 patients, but no relation was detected between cardiovascular outcomes and p66Shc expression. In patients who developed new complications at follow-up, baseline p66Shc was significantly higher, especially for macroangiopathy. The incidence of new macroangiopathy was > 3-times higher in patients with high versus those with low baseline p66Shc expression. CONCLUSIONS: p66Shc expression in PBMCs was not associated with prevalent diabetic complications but predicted new onset of complications, especially macroangiopathy, although no relation with hard cardiovascular endpoints was detected.